A companion to modern British and Irish drama, 1880-2005 - Luckhurst, Mary (Blackwell companions to literature and culture, 2006)
This wide-ranging Companion to Modern British and Irish Drama offers challenging analyses of a range of plays in their political contexts. It explores the cultural, social, economic and institutional agendas that readers need to engage with in order to appreciate modern theatre in all its complexity.An authoritative guide to modern British and Irish drama.Engages with theoretical discourses challenging a canon that has privileged London as well as white English males and realism.Topics covered include: national, regional and fringe theatres; post-colonial stages and
Keywords: English drama : 20th century : History and criticism : Handbooks, manuals, etc; English drama : Irish authors : History and criticism : Handbooks, manuals, etc; Ireland : Intellectual life : 20th century : Handbooks, manuals, etc; England : Intellectual life : 20th century : Handbooks, manuals, etc